Prognostic Nutritional Index for Predicting 3-Month Outcomes in Ischemic Stroke Patients Undergoing Thrombolysis - Xiang, Weiwei; Chen, Xiyi; Ye, Weiyi; Li, Jia; Zhang, Xu; Xie, Dewei (Frontiers in Neurology, 2020)
Objective：Malnutrition has been reported to be related to adverse prognosis in acute ischemic stroke (AIS) patients. Unfortunately, traditional nutritional assessment tools usually increase the workload of neurologists, which makes them unfeasible in the daily clinic work. We aimed to elucidate the association between the prognostic nutritional index (PNI), an easily obtainable baseline nutritional marker, and 3-month outcomes in AIS patients receiving intravenous thrombolysis (IVT). Research Methods & Procedures: The present study included 405 patients. PNI was calculated as 5*lymphocyte count (10^9 /L) + serum albumin concentration (g/L). The relationship between PNI and clinical parameters was evaluated. The multiple logistic regression model was performed to find out independent predictors of the 3-month outcomes. Results: We found that the patients in the low PNI group had a higher frequency of anemia (12.9% vs 2.3%, P＜0.001) and a higher level of the Controlling nutritional status (CONUT) score (P＜0.001). The relationship between PNI and nutrition-related factors, such as body mass index (r=0.208, P=0.001), age (r=-0.329, P＜0.001), total cholesterol (r=0.268, P＜0.001) and hemoglobin concentration (r=0.328, P＜0.001), was significant. Low PNI value (adjusted odds ratio: 2.252, confidence interval: 1.192-4.255, p=0.012) stayed as an independent predictor for the poor outcome at three months, after adjustment for potential confounders. Conclusions: The PNI was independently associated with 3-month outcomes in AIS patients undergoing IVT. As an easily obtainable nutritional marker, PNI may be a useful nutritional assessment tool in the clinic work.